A checklist of the Argidae (Hymenoptera: Symphyta: Tenthredinoidea) of Iran. (2nd January 2020) - Ghahari, Hassan; Liston, Andrew; Lee, Jong-Wook
ABSTRACT: The fauna of Iranian Argidae (Hymenoptera) is evaluated in this paper. In total, 21 species in five genera, Aproceros Malaise (one species), Aprosthema Konow (two species), Arge Schrank (14 species), Kokujewia Konow (one species) and Sterictiphora Billberg (two species), are recorded as definitely present in Iran. In addition, Sterictiphora furcata (Villers, 1789) is questionably present. The most relevant synonymies and distribution data are given. Arge pleuritica (Klug, 1834 ) is a new record for the fauna of Iran.